Study of Tempe Demand in the City of Lhokseumawe - Apridar; Rita Meutia (PT FORMOSA CENDEKIA GLOBAL, 2022)
Soybean is kind food product made from soy materials. It is consumed as the substitution food and snack. Because of high nutrient content and good flavor, soybean becomes one of high demand food every year and it is able to adapt with the consumer preference development. Commonly, the increasing of the price, actually both of fish and beef cause the consumer give the preference to soybean. The research purposes to find out variables that influence the amount of demand and the concern of demand caused by the influence variable changing. The method of analyzing is double logarithm function while the co efficiency regression directly is elasticity co efficiency from each variable. The esult of research shows that the soybean product is still under market interest. The obvious variable that influences soybean demand is the education of housewife otherwise the variable both of soybean price and fish price have given the influence of demand obviously. The relationship between the soybean demand and housewife education is more awareness of soybean nutrientthat is kept consuming as both of substitution food and snack.